Geographic Information System (GIS) Based Map Making Training in Desa Jejangkit Muara, Kabupaten Barito Kuala - Muhtar, Ghinia Anastasia; Ajeng, Ajeng; Ahmad, Sukmawati; Khotimah, Syarifah Khusnul; An-nafi, Anastasya Rosyidah (Universitas Lambung Mangkurat, 2024)
Desa Jejangkit Muara is located in Kabupaten Barito Kuala, Provinsi Kalimantan Selatan. In 2021, a flood disaster occurred, affecting 11 regencies/cities in Provinsi Kalimantan Selatan. Furthermore, in 2023, the forest and land fire disaster significantly increased, with indications of the burned area reaching 190,394.60 hectares. This study aims to provide training measured by knowledge and skills. This training is based on the results of a field study conducted by the Geography Study Program, Lambung Mangkurat University. Village communities receive GIS training to enhance their comprehension of disaster-prone areas and reduce the risks associated with fires and floods. This study employs the univariate method, which involves calculating the frequency of numbers using field-measured and calculated primary data. Research activities include training in introducing Geographic Information Systems (GIS), mapmaking, layout design, and satellite image processing using the Normalized Burn Ratio (NBR) and overlay methods. The evaluation results indicated a significant improvement in the participants' knowledge and skills during the SIG 1 training, with an average score of 57, compared to 66 and 69 for the first and second examiners, respectively. In SIG 2 training, the average was 63, while the skills of the first examiner were 60, and the second examiner was 50. The results of SIG 3 training averaged 53, while the skills of the first examiner were 55 and the second examiner was 65. This study shows the importance of ongoing training to improve community disaster preparedness and resilience.